A vanadium-enhanced polycrystalline diamond composite sheet and preparation method thereof
By adding vanadium powder to the polycrystalline diamond composite sheet and combining with WC-Co carbide substrate, using high-temperature and high-pressure sintering technology, the problem of cobalt-based polycrystalline diamond composite sheet is solved, and its wear resistance is improved It is suitable for drilling and has a more efficient drilling performance.
Patent Information
- Application Number
- CN202211479295.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-11-24
AI Technical Summary
The existing cobalt-based polycrystalline diamond composite sheets are easily graphitized or oxidized at high temperatures, and due to the large gap in thermal expansion coefficients between cobalt and diamond, the drilling effect is not ideal, especially in hard, strong abrasive and soft and hard interlaced non-corrosion. Poor performance in homogeneous strata.
Diamond powder and vanadium powder are mixed in a specific proportion, and high-temperature and high-pressure sintering is carried out through a six-sided top press, combined with WC-Co carbide substrate, vanadium-enhanced polycrystalline diamond composite sheet is prepared to improve its heat resistance and wear resistance. and impact toughness.
It significantly improves the wear resistance, impact toughness and thermal expansion critical temperature of the vanadium-enhanced polycrystalline diamond composite sheet, and is suitable for oil and gas drilling fields. The process saves diamond micropowder purification and treatment steps, saves time and labor costs, and avoids acid and alkali. pollute.
Smart Images

Figure CN115740457B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science, and in particular relates to a vanadium-enhanced polycrystalline diamond composite sheet and a preparation method thereof. Background Art
[0002] Polycrystalline Diamond Compact (PDC) is a composite material formed by sintering diamond powder on a cemented carbide substrate under high temperature and high pressure. It has the high thermal conductivity and high hardness of polycrystalline diamond and the high toughness and easy welding of cemented carbide. It is widely used in cutting tools, geological exploration drill bits, oil and gas well drill bits, etc. Although PDC has obvious advantages such as fast drilling speed and long service life in soft to medium hard and relatively homogeneous formations, its drilling effect is not ideal in hard, highly abrasive and soft and hard interlaced heterogeneous formations.
[0003] Most of the PDCs currently circulating in the market are cobalt-based polycrystalline diamond composite sheets with cobalt as a binder that is swept from a cemented carbide substrate to the diamond layer during high-temperature and high-pressure sintering. However, cobalt-based polycrystalline diamond is prone to graphitization or oxidation at high temperatures. At the same time, due to the large difference in thermal expansion coefficients between cobalt and diamond, PDC is prone to failure at high temperatures. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a vanadium-reinforced polycrystalline diamond composite sheet and a preparation method thereof, which adopts diamond micropowder as the main material, adds refractory metal vanadium powder, and utilizes a six-sided top press to synthesize a polycrystalline diamond composite sheet with heat resistance, wear resistance, and impact toughness for use in the field of oil and gas drilling at high temperature and high pressure.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] On the one hand, the present invention provides a vanadium-enhanced polycrystalline diamond composite sheet, which is sintered by a polycrystalline diamond layer and a cemented carbide substrate, wherein the polycrystalline diamond layer is prepared from the following raw materials in weight percentage: 99wt% to 99.7wt% of diamond powder and 0.3wt% to 1wt% of vanadium powder; the cemented carbide substrate is made of WC-Co cemented carbide.
[0007] Furthermore, the WC-Co cemented carbide substrate has a cobalt content of 11% to 16%, a diameter of 8 mm to 19 mm, and a thickness of 8 mm to 16 mm.
[0008] Furthermore, the diamond powder is composed of diamond particles with two particle sizes, 12 μm to 22 μm and 1 μm to 3 μm, and the weight percentage of the diamond particles with a particle size of 12 μm to 22 μm and the diamond particles with a particle size of 1 μm to 3 μm is 9:1 to ensure the densest packing density.
[0009] Furthermore, the particle size of the vanadium powder is less than 5 μm.
[0010] Another aspect of the present invention provides a method for preparing the vanadium enhanced polycrystalline diamond compact, comprising the following steps, and the following steps are performed in sequence:
[0011] Step 1: Raw material preparation:
[0012] Treat the cemented carbide substrate to remove impurities on the surface of the cemented carbide substrate and keep it ready for use;
[0013] According to the weight percentage of 99wt% to 99.7wt% of diamond micropowder and 0.3wt% to 1wt% of vanadium powder, diamond micropowder and vanadium powder are weighed respectively, put into a planetary ball mill, uniformly mixed at a ball-to-material ratio of 10:1, and then passed through a 200-mesh sieve to separate the grinding balls and the mixed powder, and the mixed powder is put into an inner tantalum cup, the cemented carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the cemented carbide substrate, and after pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0014] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, and sintering it at high temperature and high pressure to obtain a diamond composite blank;
[0015] During high temperature and high pressure sintering, the pressure is increased to 8 GPa at a rate of 2 GPa / min, the temperature is increased to 1600°C-1800°C at a rate of 30°C / s, the temperature is kept at that temperature for 240s, the temperature is decreased to room temperature at a rate of 30°C / s, and then the pressure is released to normal pressure at a rate of 1 GPa / min:
[0016] Step 3: After sandblasting, the diamond composite sheet blank obtained in step 2 is sent into a muffle furnace, and then annealed at 650° C. for 1 hour to obtain the vanadium enhanced polycrystalline diamond composite sheet.
[0017] Furthermore, in step 1, the process of treating the cemented carbide substrate to remove impurities on the surface of the cemented carbide substrate is as follows: after the cemented carbide substrate is processed to the designed size, it is sandblasted with corundum until a fresh surface is exposed, and then placed in anhydrous ethanol for ultrasonic treatment for 30 minutes to remove impurities remaining on the surface.
[0018] Furthermore, in step 1, the WC-Co cemented carbide has a cobalt content of 11% to 16%, a diameter of 8 mm to 19 mm, and a thickness of 8 mm to 16 mm.
[0019] Furthermore, in step 1, the diamond powder is composed of diamond particles with two particle sizes, namely, 12 μm to 22 μm and 1 μm to 3 μm, and the weight percentage of the diamond particles with a particle size of 12 μm to 22 μm and the diamond particles with a particle size of 1 μm to 3 μm is 9:1 to ensure the densest packing density.
[0020] Furthermore, in step 1, the particle size of the vanadium powder is less than 5 μm.
[0021] Furthermore, in the step 1, there is no liquid phase during ball milling, which is dry ball milling. Carbide balls with diameters of 6 mm and 3 mm are mixed in a weight ratio of 1:1 to form grinding balls. The ball mill jar is a carbide jar, the ball mill speed is 450 rpm, and the ball milling time is 20 min forward and 20 min reverse.
[0022] Through the above design scheme, the present invention can bring the following beneficial effects:
[0023] The vanadium-enhanced polycrystalline diamond composite sheet proposed by the present invention is made of a mixed powder consisting of diamond micropowder and vanadium powder as raw materials, and is sintered with a WC-Co cemented carbide substrate at a temperature of 1600°C to 1800°C under a high pressure of 8GPa using a conventional six-sided top press. The primary particle size of the diamond micropowder selected by the present invention is 12μm to 22μm, and the secondary particle size is 1μm to 3μm. The vanadium-enhanced polycrystalline diamond composite sheet for oil and gas drilling drill bits prepared by the present invention has high wear resistance, high impact toughness and high heat resistance.
[0024] By adopting the process of the present invention, the step of purifying the diamond powder is omitted, time and labor costs are saved, and the environmental pollution problem caused by the acid and alkali used in the purification process is avoided.
[0025] A large number of experiments have proved that the vanadium-enhanced polycrystalline diamond composite sheet proposed in the present invention has improved wear resistance and impact toughness when the amount of vanadium added is less than 0.3wt%, but both are less than 10%, and the critical temperature of thermal expansion is increased by less than 5°C. When the amount of vanadium added is greater than 3wt%, the film forming rate will be greatly affected. The present invention also has more stringent requirements on temperature. When it is lower than 1600°C, the sweeping of cobalt in the diamond layer is insufficient, resulting in the composite sheet not being formed; when it is higher than 1800°C, the sweeping of cobalt is too much, and accumulation at the interface leads to stratification. In order to prevent metallic vanadium from reacting prematurely with diamond powder, the present invention uses a temperature of 700°C to heat treat the inner assembly block, which is different from the conventional 850°C. This process saves energy while obtaining products with better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present application. The exemplary embodiments of the present invention and their descriptions are used to understand the present invention and do not constitute improper limitations of the present invention. In the drawings:
[0027] Figure 1 is an X-ray diffraction pattern of the polycrystalline diamond layer of PDC in Example 1 of the present invention;
[0028] Figure 2 is an X-ray diffraction pattern of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 2 of the present invention;
[0029] Figure 3 is an X-ray diffraction pattern of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 3 of the present invention;
[0030] Figure 4 is an X-ray diffraction pattern of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 4 of the present invention;
[0031] Figure 5 is an X-ray diffraction pattern of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 5 of the present invention;
[0032] Figure 6 is an X-ray diffraction pattern of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 6 of the present invention;
[0033] Figure 7 This is an X-ray diffraction diagram of the polycrystalline diamond layer of the vanadium enhanced polycrystalline diamond compact in Example 7 of the present invention. DETAILED DESCRIPTION
[0034] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs.
[0035] To avoid obscuring the essence of the present invention, well-known methods, procedures, processes, components and circuits have not been described in detail.
[0036] It should be noted that in Examples 1-7, the cemented carbide substrate is made of WC-Co cemented carbide. Furthermore, the WC-Co cemented carbide has a cobalt content of 11% to 16%, a diameter of 8 mm to 19 mm, and a thickness of 8 mm to 16 mm.
[0037] Example 1 (control group)
[0038] The specific steps of the method for preparing a polycrystalline diamond composite sheet in this example are as follows:
[0039] Step 1: Raw material preparation:
[0040] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0041] ② According to the weight percentage of 90wt% diamond particles with a particle size of 12μm to 22μm and 10wt% diamond particles with a particle size of 1μm to 3μm, in a planetary ball mill, dry ball milling is used, and carbide balls with diameters of 6mm and 3mm are mixed in a weight ratio of 1:1 to form grinding balls. At a ball-to-material ratio of 10:1, the rotation speed is 450rpm, forward for 20min, reverse for 20min, and after uniform mixing, the grinding balls and the mixed powder are separated through a 200-mesh sieve, and the mixed powder is loaded into an inner tantalum cup, the carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the carbide substrate. After pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0042] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1800°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0043] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfers of the polycrystalline diamond layer and the cemented carbide substrate, and the sizes are all 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, obtain a polycrystalline diamond composite.
[0044] The performance indicators of the polycrystalline diamond composite sheet prepared in this example were tested as follows: vertical lathe wear ratio was 1.11 million, impact toughness was 1680 J, and critical temperature of thermal expansion of the polycrystalline diamond layer was 842°C. Figure 1An X-ray diffraction pattern of the polycrystalline diamond layer of the PDC of this example is shown.
[0045] Example 2
[0046] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0047] Step 1: Raw material preparation:
[0048] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0049] ② According to the weight percentage of 89.73wt% diamond particles with a particle size of 12μm to 22μm, 9.97wt% diamond particles with a particle size of 1μm to 3μm and 0.3wt% vanadium powder, in a planetary ball mill, dry ball milling is used, and carbide balls with diameters of 6mm and 3mm are mixed in a weight ratio of 1:1 to form grinding balls, with a ball-to-material ratio of 10:1, at a speed of 450rpm, forward for 20min, reverse for 20min, and after uniform mixing, pass through a 200-mesh sieve to separate the grinding balls and the mixed powder, and put the mixed powder into an inner tantalum cup, place the carbide substrate above the mixed powder, and buckle the outer tantalum cup on the carbide substrate, pre-press at a pressure of 3MPa on a hydraulic press, and then place in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0050] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1800°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0051] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0052] The performance indicators of the vanadium-enhanced polycrystalline diamond composite sheet prepared in this example were tested: vertical lathe wear ratio of 1.59 million, impact toughness of 3420J, and critical temperature of thermal expansion of the polycrystalline diamond layer of 859°C, which were respectively increased by 43.2%, 104%, and 17°C compared with the control group.
[0053] Example 3
[0054] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0055] Step 1: Raw material preparation:
[0056] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0057] ② According to the weight percentage of 89.46wt% diamond particles with a particle size of 12μm to 22μm, 9.94wt% diamond particles with a particle size of 1μm to 3μm and 0.6wt% vanadium powder, dry ball milling is used in a planetary ball mill, and carbide balls with diameters of 6mm and 3mm are mixed in a weight ratio of 1:1 to form grinding balls, with a ball-to-material ratio of 10:1, at a speed of 450rpm, forward rotation for 20min, reverse rotation for 20min, and after uniform mixing, the grinding balls and the mixed powder are separated through a 200-mesh sieve, and the mixed powder is loaded into an inner tantalum cup, the carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the carbide substrate, and after pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0058] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1600°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0059] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0060] The performance indicators of the vanadium-enhanced polycrystalline diamond composite sheet prepared in this example were tested: vertical lathe wear ratio of 1.75 million, impact toughness of 4570J, and critical temperature of thermal expansion of the polycrystalline diamond layer of 865°C, which were respectively increased by 57.7%, 172%, and 23°C compared with the control group.
[0061] Example 4
[0062] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0063] Step 1: Raw material preparation:
[0064] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0065] ② According to the weight percentage of 89.19wt% diamond particles with a particle size of 12μm to 22μm, 9.91wt% diamond particles with a particle size of 1μm to 3μm and 0.9wt% vanadium powder, in a planetary ball mill, dry ball milling method is adopted, using cemented carbide balls with diameters of 6mm and 3mm, mixed in a weight ratio of 1:1 to form grinding balls, and the grinding balls and the mixed powder are separated at a ball-to-material ratio of 10:1, and the mixed powder is loaded into an inner tantalum cup, and the cemented carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the cemented carbide substrate, and after pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0066] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1700°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0067] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0068] The performance indicators of the vanadium-enhanced polycrystalline diamond composite sheet prepared in this example were tested as follows: vertical lathe wear ratio of 1.866 million, impact toughness of 4990J, critical temperature of thermal expansion of the polycrystalline diamond layer of 868°C, which were respectively increased by 68.1%, 197%, and 26°C compared with the control group.
[0069] Example 5
[0070] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0071] Step 1: Raw material preparation:
[0072] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0073] ② According to the weight percentage of 89.1wt% diamond particles with a particle size of 12μm to 22μm, 9.9wt% diamond particles with a particle size of 1μm to 3μm and 1wt% vanadium powder, dry ball milling is used in a planetary ball mill to mix carbide balls with diameters of 6mm and 3mm in a weight ratio of 1:1 to form grinding balls, and the grinding balls and the mixed powder are separated at a ball-to-material ratio of 10:1, and the mixed powder is loaded into an inner tantalum cup, and the carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the carbide substrate, and after pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0074] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1700°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0075] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0076] The performance indicators of the vanadium-enhanced polycrystalline diamond composite sheet prepared in this example were tested as follows: vertical lathe wear ratio of 1.87 million, impact toughness of 5270J, critical temperature of thermal expansion of the polycrystalline diamond layer of 870°C, which were respectively increased by 68.5%, 214%, and 28°C compared with the control group.
[0077] Example 6
[0078] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0079] Step 1: Raw material preparation:
[0080] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0081] ② According to the weight percentage of 88.2wt% diamond particles with a particle size of 12μm to 22μm, 9.8wt% diamond particles with a particle size of 1μm to 3μm and 2wt% vanadium powder, dry ball milling is used in a planetary ball mill to mix carbide balls with diameters of 6mm and 3mm in a weight ratio of 1:1 to form grinding balls, and the grinding balls and the mixed powder are separated at a ball-to-material ratio of 10:1. The mixed powder is loaded into an inner tantalum cup, the carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the carbide substrate. After pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0082] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1700°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0083] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0084] The performance indicators of the vanadium-enhanced polycrystalline diamond composite sheet prepared in this example were tested as follows: vertical lathe wear ratio of 1.68 million, impact toughness of 4850J, critical temperature of thermal expansion of the polycrystalline diamond layer of 876°C, which were respectively increased by 51.4%, 189%, and 34°C compared with the control group.
[0085] Example 7
[0086] In this example, a method for preparing a vanadium-enhanced polycrystalline diamond composite sheet has the following specific steps:
[0087] Step 1: Raw material preparation:
[0088] ① After the cemented carbide substrate is processed into a blank with a diameter of 18 mm and a height of 15 mm, it is sandblasted with corundum until a fresh surface is exposed, and then ultrasonically treated in anhydrous ethanol for 30 minutes to remove impurities remaining on the surface and set aside;
[0089] ② According to the weight percentage of 87.3wt% diamond particles with a particle size of 12μm to 22μm, 9.7wt% diamond particles with a particle size of 1μm to 3μm and 3wt% vanadium powder, dry ball milling is used in a planetary ball mill, and carbide balls with diameters of 6mm and 3mm are mixed in a weight ratio of 1:1 to form grinding balls. At a ball-to-material ratio of 10:1, the rotation speed is 450rpm, and the mixture is passed through a 200-mesh sieve to separate the grinding balls and the mixed powder. The mixed powder is placed in an inner tantalum cup, the carbide substrate is placed above the mixed powder, and an outer tantalum cup is buckled on the carbide substrate. After pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block;
[0090] Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, increasing the pressure to 8 GPa at a rate of 2 GPa / min, increasing the temperature to 1800°C at a rate of 30°C / s, keeping the temperature for 240s, cooling to room temperature at a rate of 30°C / s, and then unloading the pressure to normal pressure at a rate of 1 GPa / min to complete high temperature and high pressure sintering to obtain a diamond composite blank;
[0091] Step 3, after sandblasting the diamond composite blank obtained in step 2, send it into a muffle furnace, and then anneal it at 650°C for 1h, grind the surface of the polycrystalline diamond layer, process the outer diameter to 16mm, grind the thickness of the polycrystalline diamond layer to 2.2mm~2.4mm, machine the bottom surface of the cemented carbide substrate to a diamond composite height of 13mm, machine the chamfer of the polycrystalline diamond layer and the chamfer of the cemented carbide substrate, and the size is 0.38mm / 45°, polish the outer diameter and bottom surface of the PDC, and after a series of the above processes, a vanadium enhanced polycrystalline diamond composite sheet is obtained.
[0092] The performance indicators of the vanadium powder reinforced polycrystalline diamond composite sheet prepared in this example were tested as follows: vertical lathe wear ratio of 1.57 million, impact toughness of 2760J, critical temperature of thermal expansion of polycrystalline diamond layer of 887°C, which were respectively increased by 41.4%, 64%, and 45°C compared with the control group.
[0093] The polycrystalline diamond composite sheet prepared in the above-mentioned embodiment 1 and the vanadium-enhanced polycrystalline diamond composite sheet prepared in embodiments 2-7 were tested for wear resistance, impact toughness, and thermal expansion coefficient under the same test conditions. The test methods all adopted the conventional test methods of domestic composite sheet manufacturers. A vertical granite lathe was used for wear resistance test, and the rock penetration depth was 0.25mm. A drop hammer impact device was used for impact resistance test. The test angle was the same as the wear resistance test, both of which were 15°, and the single impact energy was 60J until the sample was broken. A thermal expansion coefficient tester was used to measure the thermal expansion coefficient. The setting conditions were air heating, the starting temperature was 30°C, the heating rate was 5.4°C / min, and the temperature was raised to 1000°C.
[0094] The performance enhancement principle of the vanadium-enhanced polycrystalline diamond composite sheet proposed in the present invention is as follows:
[0095] Vanadium reacts with diamond to form V8C7 in situ under high temperature and high pressure, and forms two reinforcing phases Co3V with Co swept across the WC-Co based cemented carbide substrate, see Figures 2 to 7 X-ray diffraction patterns of the polycrystalline diamond layer of the vanadium-enhanced polycrystalline diamond composite sheet of Example 2-7. V8C7 is a commonly used reinforcing phase in the field of materials, but the strengthening effect of Co3V on wear resistance, impact toughness and heat resistance in the field of materials has not been reported. Examples 2-7 of the present invention show that by adding vanadium, the wear resistance, impact toughness and heat resistance of the composite sheet can be significantly improved, as shown in Table 1 for the mechanical properties comparison of Examples 1-7.
[0096] Table 1 Comparison of mechanical properties of Examples 1-7
[0097]
[0098] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A vanadium-enhanced polycrystalline diamond composite sheet, which is sintered by a polycrystalline diamond layer and a cemented carbide substrate, characterized in that: The polycrystalline diamond layer is prepared from the following raw materials in weight percentage: 99wt% to 99.7wt% of diamond powder and 0.3wt% to 1wt% of vanadium powder; the cemented carbide substrate is made of WC-Co cemented carbide; the cobalt content of the WC-Co cemented carbide substrate is 11% to 16%, the diameter is 8 mm to 19 mm, and the thickness is 8 mm to 16 mm; The diamond micropowder is composed of diamond particles with two particle sizes, 12 μm to 22 μm and 1 μm to 3 μm, and the weight percentage of the diamond particles with a particle size of 12 μm to 22 μm and the diamond particles with a particle size of 1 μm to 3 μm is 9:1; The particle size of the vanadium powder is less than 5 μm.
2. A method for preparing the vanadium enhanced polycrystalline diamond compact according to claim 1, characterized in that: The process includes the following steps, which are performed in sequence: Step 1: Raw material preparation: Treat the cemented carbide substrate to remove impurities on the surface of the cemented carbide substrate and keep it ready for use; According to the weight percentage of 99wt% to 99.7wt% of diamond micropowder and 0.3wt% to 1wt% of vanadium powder, diamond micropowder and vanadium powder are weighed respectively, put into a planetary ball mill, uniformly mixed at a ball-to-material ratio of 10:1, and then passed through a 200-mesh sieve to separate the grinding balls and the mixed powder, and the mixed powder is put into an inner tantalum cup, the cemented carbide substrate is placed on the mixed powder, and an outer tantalum cup is buckled on the cemented carbide substrate, and after pre-pressing at a pressure of 3MPa on a hydraulic press, it is placed in a vacuum furnace for heat treatment at 700°C for 2h to obtain an inner assembly block; Step 2, placing the inner assembly block in a salt tube, wrapping the salt tube with magnesium oxide, and then assembling it with a graphite tube and pyrophyllite to obtain an outer assembly block, placing the outer assembly block in a six-sided top press, and sintering it at high temperature and high pressure to obtain a diamond composite blank; During high temperature and high pressure sintering, the pressure is increased to 8 GPa at a rate of 2 GPa / min, the temperature is increased to 1600°C-1800°C at a rate of 30°C / s, the temperature is kept at that temperature for 240s, the temperature is decreased to room temperature at a rate of 30°C / s, and then the pressure is released to normal pressure at a rate of 1 GPa / min: Step 3: After sandblasting, the diamond composite sheet blank obtained in step 2 is sent into a muffle furnace, and then annealed at 650° C. for 1 hour to obtain the vanadium enhanced polycrystalline diamond composite sheet.
3. The method according to claim 2, characterized in that: In the step 1, the process of treating the cemented carbide substrate to remove impurities on the surface of the cemented carbide substrate is as follows: after the cemented carbide substrate is processed to the designed size, it is sandblasted with corundum until a fresh surface is exposed, and then placed in anhydrous ethanol for ultrasonic treatment for 30 minutes to remove impurities remaining on the surface.
4. The method according to claim 2, characterized in that: In the step 1, there is no liquid phase during ball milling, which is dry ball milling. Carbide balls with diameters of 6 mm and 3 mm are mixed in a weight ratio of 1:1 to form grinding balls. The ball mill jar is a carbide jar, the ball mill speed is 450 rpm, and the ball milling time is 20 minutes in forward rotation and 20 minutes in reverse rotation.